2017
DOI: 10.11131/2017/101363
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antifibrotic Effect of Serotonin Receptor Antagonists on Bleomycin Induced Pulmonary Fibrosis in Rats

Abstract: Idiopathic pulmonary fibrosis (IPF) is believed to be an epithelial-fibroblast disease. Activated epithelial cells are thought to release potent fibrogenic molecules and cytokines, such as tumor necrosis factor-alpha (TNF-α) and transforming growth factor-beta1 (TGF-β1), which in turn foster the transformation of fibroblasts into myofibroblasts and promote production of extracellular matrix molecules and so collagen deposition. Serotonin (5-hydroxy tryptamine, 5-HT) is an important mediator for lung fibrogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Further studies suggested that the antiproliferative effects of EXT5 and EXT9 were related to the pAkt/p21 signaling pathway [38]. It is worth mentioning that in vivo studies in the BLM-induced pulmonary fibrosis rat model showed that 5-HT 2C R and 5-HT 7 R were also implicated in pulmonary fibrosis [37,47,48].…”
Section: Pulmonary Fibrosismentioning
confidence: 97%
See 1 more Smart Citation
“…Further studies suggested that the antiproliferative effects of EXT5 and EXT9 were related to the pAkt/p21 signaling pathway [38]. It is worth mentioning that in vivo studies in the BLM-induced pulmonary fibrosis rat model showed that 5-HT 2C R and 5-HT 7 R were also implicated in pulmonary fibrosis [37,47,48].…”
Section: Pulmonary Fibrosismentioning
confidence: 97%
“…The 5-HT 2B R has been implicated in fibrotic disorders such as liver fibrosis [31][32][33], pulmonary fibrosis [34][35][36][37][38], systemic sclerosis (SSc) [39][40][41][42][43], and pancreatic fibrosis [44].…”
Section: Fibrosis Disordersmentioning
confidence: 99%
“…Rats of HCC were administered intraperitoneal (IP) a single dose of DEN (200 mg/kg dissolved in normal saline 0.9% at a final volume of 1ml/kg. Two weeks after DEN challenging, CCl4 solution (CCl4/olive oil; 1:1; 1 ml/kg) was administered IP three times weekly for 6 consecutive weeks (Elaidy et al, 2017). After detection of HCC development, the treatment by sorafenib and anthraquinones were done.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…In the cardiovascular system, 5-HT 2B is expressed in myocardial, endothelial, and vascular smooth muscle cells, and agonism is involved in cardiovascular diseases including cardiomyopathy, valvular heart disease (VHD), and pulmonary arterial hypertension. , Drug-induced VHD was the cause of the withdrawal of fenfluramine and dexfenfluramine used for the indication of obesity from the U.S. market in 1997 and pergolide used for the indication of Parkinson’s disease in 2007. These compounds are partial or full agonists of 5-HT 2B with high affinity, and the pathogenesis of drug-induced VHD could be correlated with off-target activation of 5-HT 2B . ,, Furthermore, 5-HT 2B could be linked to the vascular heart diseases such as mitral valve prolapse and its involvement in calcific aortic valve disease; , fibrosis disorders such as liver fibrosis, pulmonary fibrosis, systemic sclerosis, and pancreatic fibrosis; different types of cancer including hepatocellular carcinoma, neuroendocrine tumor, , and pancreatic ductal adenocarcinomas; and irritable bowel syndrome of the gastrointestinal tract. …”
Section: Introductionmentioning
confidence: 99%